The impact of a structured polygraphy screening incorporated in a novel remote mobile health pathway on sleep apnoea prevalence in patients with atrial fibrillation. (19th May 2022) - Verhaert, D; Betz, K; Gawalko, M; Hermans, ANL; Van Der Velden, RMJ; Westra, SW; Schotten, U; Hendriks, JM; Vernooy, K; Linz, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Untreated obstructive sleep apnoea (OSA) contributes to progression of atrial fibrillation (AF) and reduces the success rate of heart rhythm control strategies. OSA remains one of the most frequently underdiagnosed modifiable risk factors in AF patients due to a lack of standardized screening methods and low awareness. Purpose: To assess the impact of implementation of a structured remote OSA screening and management pathway on the prevalence of OSA in AF patients scheduled for AF ablation procedures. Methods: In October 2020, a novel remote OSA screening and management pathway (VIRTUAL-SAFARI) was introduced in two AF outpatient clinics in the Netherlands. Consecutive patients scheduled for AF ablation were offered OSA screening consisting of sending a portable home sleep test to patients' homes to perform a remote sleep recording for one night, analysis by a sleep physician, discussion of results with the patient, and initiation of treatment (when applicable). The impact of this structural screening strategy was assessed by comparing the prevalence of concomitant OSA (defined as apnoea-hypopnoea index ≥5) for patients scheduled for AF ablation in the year before and after introduction of the OSA management pathway. Results: A total of 733 patients was studied, 308 in the year before (Oct '19 - Sep '20) and 425 in the year after (Oct '20 - Sep '21) introduction of the VIRTUAL-SAFARI pathway. Median age was 65 [58-71], 64% was male and median body mass index (BMI) was 27 [25-30] kg/m2. Baseline characteristics were comparable for the groups before and after introduction of the pathway (Table 1). In the cohort before pathway introduction, OSA had been diagnosed in 26 patients (8%, Figure 1) and was treated with positive airway pressure in 10 cases (3%). In the cohort after pathway introduction, OSA had previously been diagnosed in 53 patients (12%). Eighty-eight percent of patients without previous OSA screening was referred via the remote pathway. Results of the sleep recordings were available for 213 (59%) at the time of this analysis. Previously unknown OSA was diagnosed in 184 patients (86% of available recordings), increasing the prevalence of confirmed OSA to 237 (55%). For 22% of patients, results of sleep recordings are pending. Absence of OSA was confirmed in 9%, and 13% of patients had not been screened (e.g. because of patient preference or logistical reasons). After pathway introduction, 82 patients (19%) were treated or received advice to start treatment with positive airway pressure. Treatment decisions are pending for 9% of the cohort. Conclusion: After the implementation of structured remote OSA screening in a well characterized cohort of consecutive patients scheduled for AF ablation, the prevalence of diagnosed OSA increased from 8% to 55%. Whether appropriate risk factor management, including treatment of OSA identified by structured screening, will improve AF outcomes needs to be tested in future studies.